2017
DOI: 10.7759/cureus.1370
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction in Young Systemic Lupus Erythematosus Patient with Normal Coronary Arteries

Abstract: A 34-year-old female with a past medical history of systemic lupus erythematosus (SLE) and a deep venous thrombosis experienced substernal chest pain for 24 hours. Her physical exam was remarkable for brown macular rash over the face. Her initial electrocardiogram showed ST depression in lead V3–V6 along with an elevated troponin I level of 1.23 ng/dl (normal 0.0–0.4) that increased to 2.33 ng/dl in a four-hour duration. Cardiac catheterization revealed mild 10–20% focal plaque in the mid left anterior descend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…These non-atherosclerotic variations can create a diagnostic dilemma as they show an absence of atherosclerotic plaque on coronary angiography. However, the use of endomyocardial biopsy and/or echocardiography can be valuable in identifying the underlying cause [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These non-atherosclerotic variations can create a diagnostic dilemma as they show an absence of atherosclerotic plaque on coronary angiography. However, the use of endomyocardial biopsy and/or echocardiography can be valuable in identifying the underlying cause [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic inflammatory disease of unknown cause that can affect the skin, joints, lungs, nervous system, serous membranes, and/or other organs of the body [ 1 ]. SLE has been associated with an increased risk of cardiovascular disease, including ischemic heart disease (IHD), which affects up to 16% of patients with the condition [ 2 ]. Among patients with SLE, IHD is commonly attributed to atherosclerosis, which is more prevalent due to systemic inflammation and the adverse effects of long-term glucocorticoid treatment [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…La enfermedad coronaria que se manifiesta como infarto agudo de miocardio es hasta nueve veces más frecuente en los pacientes con LES que en la población general, llegando a ser hasta 50 veces mayor en las mujeres con LES en edades entre los 35 y 44 años comparadas con población sana del mismo sexo y la misma edad 4 . De igual forma se debe tener en cuenta que, en los pacientes con LES y SAF, hasta el 75% de los episodios de infarto agudo de miocardio tienen coronarias sanas, mientras que solo en un 25% se evidencia estenosis significativa 5 ; esto se relaciona directamente con el tiempo de evolución de la enfermedad (LES y SAF), ya que se ha encontrado que con menor tiempo de evolución de la enfermedad los eventos coronarios se relacionan principalmente con arteritis coronaria, miocarditis, trombosis coronaria o embolización con recanalización espontanea 6 , mientras que en aquellos pacientes con mayor tiempo de evolución de la enfermedad se observa un desarrollo acelerado de ateroesclerosis coronaria, relacionada con valores elevados de colesterol y triglicéridos, y valores más bajos de lipoproteínas de alta densidad, comparados con la población general de la misma edad y el mismo sexo 2 .…”
Section: Discussionunclassified
“…On the other hand, there are reported cases of transmural myocardial infarction in SLE patients with angiographically normal coronary arteries. Farooq et al , 3 who reported one of such cases, hypothesized that coronary microcirculation vasculitis could have been the aetiology of the AMI. Microcirculation thrombosis, demonstrated on histology, was also assumed as a possible cause of myocardial infarction in a young SLE patient in the case described by Curtis et al , 4 in which the clinical presentation was an acute papillary muscle rupture.…”
Section: Discussionmentioning
confidence: 99%